Effect of Ownership Structure on Corporate Social Responsibility Disclosure on SRI-KEHATI Index Companies Listed on Indonesia Stock Exchange - Annisa Afdila; Yolandafitri Zulvia (Financial Management Studies, 2022)
The study aims to analyze the influence (1) of ownership structures with managerial ownership proxies, (2) ownership structures with institutional ownership proxies and (3) ownership structures with foreign ownership proxies on corporate social responsibility (CSR) disclosures on SRI-KEHATI index companies listed on the Indonesia Stock Exchange in 2016-2020. The study used three control variables: profitability, leverage, and firm size. The population in this study is all companies that include the SRI-KEHATI index listed on the Indonesia Stock Exchange. While the samples in the study were determined by the purposive sampling method, the company's samples for five consecutive years from 2016-2020, resulting in a samples count of 18 companies with 90 observations for each variable. The analysis method used is multiple linear regression analysis using the IBM SPSS Statistics 25 program.. The results of this study concluded that (1) ownership structures with managerial ownership proxies have a negative and insignificant effect on CSR disclosure, (2) ownership structure with institutional ownership proxy positive and significant on CSR disclosure, (3) ownership structure with foreign ownership proxy negative and insignificant on CSR disclosure on SRI-KEHATI index companies listed on Indonesia Stock Exchange